2018
DOI: 10.1155/2018/4095473
|View full text |Cite
|
Sign up to set email alerts
|

Robust Linear Output Regulation Using Extended State Observer

Abstract: This paper presents a disturbance rejection-based solution to the problem of robust output regulation. The mismatch between the underlying plant and its nominal mathematical model is formulated by two disturbance classes. The first class is assumed to be generated by an autonomous linear system while for the second class no specific dynamical structure is considered. Accordingly, the robustness of the closed-loop system against the first disturbance class is achieved by following the internal model principle. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Actually, the output-feedback SMC for PMSM servo system subject to unknown load torque disturbances is a challenging problem, since it is difficult to estimate both the unmeasured states and the unmatched disturbance at the same time. Reference [35] gives a new idea for outputfeedback SMC design, which combines SMC with the basic idea of output regulation theory [36,37]. Inspired by [35], this paper aims to solve the output-feedback SMC problem for PMSM servo system subject to unmatched disturbances.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, the output-feedback SMC for PMSM servo system subject to unknown load torque disturbances is a challenging problem, since it is difficult to estimate both the unmeasured states and the unmatched disturbance at the same time. Reference [35] gives a new idea for outputfeedback SMC design, which combines SMC with the basic idea of output regulation theory [36,37]. Inspired by [35], this paper aims to solve the output-feedback SMC problem for PMSM servo system subject to unmatched disturbances.…”
Section: Introductionmentioning
confidence: 99%
“…Further new immersion and invariance observer for inertial MEMS attitude-heading reference systems, an enhanced fuzzy H∞ estimation algorithm [20,21] and nonlinear disturbance rejection-based controller of a triaxial MEMS vibratory gyroscope [22,23] are presented. The nonlinear control [24][25][26][27][28][29][30], linear and nonlinear observer and filters [31][32][33][34][35][36][37][38][39][40] and predictive techniques [41][42][43] properly explained space mechanism related control systems.…”
Section: Introductionmentioning
confidence: 99%
“…In [4], the authors have shown that researchers have developed some methods for the solution of large-scale Sylvester equations [5][6][7]. On the other hand, several research studies for solving the Sylvester algebraic equation have gained attention in engineering problem [8][9][10]. In the image-processing problem, the presentation developed in [8] has shown that the image fusion method applied to a large-scale image facilitates reduction of computational complexity based on the explicit solution of large-scale Sylvester equations.…”
Section: Introductionmentioning
confidence: 99%
“…In the image-processing problem, the presentation developed in [8] has shown that the image fusion method applied to a large-scale image facilitates reduction of computational complexity based on the explicit solution of large-scale Sylvester equations. Furthermore, many problems of control theory such as regulator problem [9] and particle swarm theory [10] lead to a Sylvester equation.…”
Section: Introductionmentioning
confidence: 99%